2020
DOI: 10.1111/1440-1681.13394
|View full text |Cite
|
Sign up to set email alerts
|

High‐sucrose diet potentiates hyperaldosteronism and renal injury induced by stress in young adult rats

Abstract: Analyze the effect of stress and high‐sucrose diet on serum aldosterone levels and the morphometric characteristics of the kidney in young adult rats. Wistar male rats aged 21 days old weaned were randomly assigned into four groups: control (C), stressed (St), high‐sucrose diet (S30), and chronic restraint stress plus a 30% sucrose diet (St + S30). Rats were fed with a standard chow and tap water ad libitum (C group) or 30% sucrose diluted in water (S30 group) during eight weeks. The St and St + S30 groups wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Many of these macronutrient studies used doi: https://doi.org/10.15407/ubj94.01.105 a nutritional geometry approach, where the effects of macronutrients, calories, and food interrogated across a wide topology of diets differing in macronutrient content [3]. It is shown that metabolic disorders under the conditions of excessive consumption of sucrose occur in the cells of the liver, pancreas, kidneys, accompanied by the development of dyslipidemia and hyperglycemia [1,4]. Persistent chronic hyperglycemia is known to contribute to the develop ment and progression of diabetic nephropathy [5].…”
mentioning
confidence: 99%
“…Many of these macronutrient studies used doi: https://doi.org/10.15407/ubj94.01.105 a nutritional geometry approach, where the effects of macronutrients, calories, and food interrogated across a wide topology of diets differing in macronutrient content [3]. It is shown that metabolic disorders under the conditions of excessive consumption of sucrose occur in the cells of the liver, pancreas, kidneys, accompanied by the development of dyslipidemia and hyperglycemia [1,4]. Persistent chronic hyperglycemia is known to contribute to the develop ment and progression of diabetic nephropathy [5].…”
mentioning
confidence: 99%